COMPARATIVE ANALYSIS OF ETHICAL CONSIDERATIONS IN TRANSLATING SENSITIVE MEDIA TEXTS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
In the globalized world of the 21st century, media texts cross linguistic and cultural boundaries more frequently than ever before. Translators play a crucial role in this process, ensuring that news is accessible to audiences beyond the source language. However, translating media texts, especially those covering sensitive topics such as crime, politics, or personal tragedies, presents unique ethical dilemmas. These challenges are further complicated when translating between languages with distinct cultural, political, and historical contexts, such as Uzbek and English. This paper aims to explore the ethical considerations that arise in the translation of sensitive media texts from Uzbek to English and vice versa. Through case studies and comparative analysis, the study highlights how cultural norms, political environments, and journalistic standards influence translation practices. The focus will be on how translators navigate issues of bias, censorship, privacy, and cultural sensitivity when dealing with sensitive content.